Barcoding Life to Conserve Biological Diversity: Beyond the Taxonomic Imperative - Vernooy, Ronnie (Public Library of Science, 2010)
Barcoding scientists aspire to adhere to the objectives of the Convention on Biological Diversity by promoting conservation, sustainability, and the equitable sharing of benefits arising from use of genetic resources. (Image: Juan Manuel Escalante, wwww.realitat.com)